2021
DOI: 10.1289/ehp8152
|View full text |Cite|
|
Sign up to set email alerts
|

Rare, Protein-Altering Variants in AS3MT and Arsenic Metabolism Efficiency: A Multi-Population Association Study

Abstract: Background: Common genetic variation in the arsenic methyltransferase ( AS3MT ) gene region is known to be associated with arsenic metabolism efficiency (AME), measured as the percentage of dimethylarsinic acid (DMA%) in the urine. Rare, protein-altering variants in AS3MT could have even larger effects on AME, but their contribution to AME has not been investigated. Objectives: We estimated the impact of rare, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(159 reference statements)
1
7
0
Order By: Relevance
“…This study builds on previous work in the 10q24.32 region [ 29 , 31 , 49 , 54 , 55 ] in several ways. Previous studies have found signs of positive selection near the AS3MT gene associated with efficient arsenic metabolism [ 56 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This study builds on previous work in the 10q24.32 region [ 29 , 31 , 49 , 54 , 55 ] in several ways. Previous studies have found signs of positive selection near the AS3MT gene associated with efficient arsenic metabolism [ 56 ].…”
Section: Discussionmentioning
confidence: 85%
“…Data were analyzed using PLINK v1.9 [ 70 ] for SHS and NHSCS and using Genome-wide Complex Train Analysis (GCTA) [ 72 ] for HEALS to allow adjustment for cryptic relatedness using a genetic relationship matrix in a linear mixed model [ 28 , 31 , 54 , 72 , 73 ]. To generate this kinship matrix, we used genome-wide SNP data available for 2,434 HEALS participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since arsenic metabolites were not measured in HCHS/SOL, the first assumption cannot be directly tested. However, its plausibility is supported first by the multiple study populations in which variation near the AS3MT region has convincingly been associated with iAs metabolism 15 , 17 , 18 , 74 , 75 . Additionally, the SNVs selected for the instrument belong to biological pathways that are known to be involved in arsenic metabolism efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…11 Prior GWA studies of Bangladeshi individuals have identified independent associations of four SNPs (single nucleotide polymorphisms) with AME: three in the 10q24.32/ AS3MT region (rs4919690, rs11191492, and rs191177668) and one in the FTCD gene (rs61735836). 12,18,19 The FTCD gene plays an important role in histidine catabolism, which generates one-carbon units that can enter the one-carbon/folate cycle, which in turn provides methyl groups for arsenic metabolism. 12 All four of these SNPs are independently associated with urine DMA%.…”
mentioning
confidence: 99%